2017
DOI: 10.5588/ijtld.17.0062
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and hazardous/harmful alcohol use are prevalent and correlate with stigma among TB-HIV patients in Lesotho

Abstract: SUMMARY SETTING Limited data exist on the prevalence and correlates, including stigma, of mental health conditions, including depressive symptoms and alcohol use, among patients co-infected with tuberculosis (TB) and the human immunodeficiency virus (HIV) in sub-Saharan Africa, despite their negative impact on health outcomes. OBJECTIVE To assess the prevalence and correlates of depressive symptoms and hazardous/harmful alcohol use among TB-HIV patients in the Start TB patients on ART and Retain on Treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 29 publications
3
42
2
Order By: Relevance
“…Among twenty-seven studies (11,14,15,17,25, included in the present meta-analysis, only eight (11,14,25,36,37,39,45,49) reported about the associated factors for alcohol use disorder among tuberculosis patients. Our qualitative synthesis for the socio-demographic factors associated with AUD in tuberculosis patients revealed that male gender (14,25,36,39,49), age older than 35 years (14), being single, divorced or widowed (11,14), being unemployed (11), being black American (36), colored ethnicity (49), low level of education (14,49), no educational background (39), low level of income (< Rs 5000 per month) (14) and poverty (49).…”
Section: Factors Associated With Alcohol Use Disorder Among Tuberculomentioning
confidence: 96%
See 4 more Smart Citations
“…Among twenty-seven studies (11,14,15,17,25, included in the present meta-analysis, only eight (11,14,25,36,37,39,45,49) reported about the associated factors for alcohol use disorder among tuberculosis patients. Our qualitative synthesis for the socio-demographic factors associated with AUD in tuberculosis patients revealed that male gender (14,25,36,39,49), age older than 35 years (14), being single, divorced or widowed (11,14), being unemployed (11), being black American (36), colored ethnicity (49), low level of education (14,49), no educational background (39), low level of income (< Rs 5000 per month) (14) and poverty (49).…”
Section: Factors Associated With Alcohol Use Disorder Among Tuberculomentioning
confidence: 96%
“…The average prevalence of alcohol use disorder in tuberculosis patients was higher in Asia and Europe;37% (14, 17, 25, 35-39, 42-45, 48, 53) than the prevalence in US ; 24% (36,39) and Africa ; 24% (11,15,33,34,40,41,46,47,(49)(50)(51)(52)54) (Figure 3). The average prevalence of AUD was 36% in studies that do not report the assessment tool for AUD (35,36,38,(41)(42)(43)(44)51) which is higher than the prevalence in studies that utilized AUDIT (26%) (14,15,17,25,34,39,(45)(46)(47)(48)(49)(50)(52)(53)(54) (Figure 4). Besides, studies which were case-control (15,40,42) provided higher prevalence of AUD (39%) than cross-sectional (11,14,17…”
Section: Subgroup Analysis Of the Prevalence Of Alcohol Use Disorder mentioning
confidence: 98%
See 3 more Smart Citations